Bridge’s Overall Structural Scheme Analysis in High Seismic Risk Permafrost Regions - Zhihua Xiong; Jianbing Chen; Chen Liu; Jinping Li; Wenwen Li (Salehan Institute of Higher Education, 2022)
The mechanism of pile-soil reaction in frozen ground is not clear at present, but it is obvious that the reduction of dead weight will be beneficial to the seismic resistance of bridges. In view of the limited bridge engineering practice in high seismic risk permafrost regions, the paper addressed the structural performance of the superstructure and its effect on piles in these special regions. Four superstructures with different dead weights were compared, and bored piles were designed. Numerical simulations were implemented to investigate the refreezing time of the bored pile foundation. The concrete pile cooled rapidly in the first two days. The refreezing times of the GFRP, prestressed concrete T-girder, integrated composite girder, and MVFT girder were 15d, 37d, 39d, and 179d, respectively. The refreezing time of a pile in the same soil layer is mainly affected by the pile’s diameter, and it is significantly correlated to the square of the pile diameter. It reflects that the selection of bridge superstructures in the permafrost region is very important, which has been ignored in previous studies. The pile length and pile diameter of the lighter superstructure can be shorter and smaller to reduce the refreezing time and alleviate the thermal disturbance. Doi: 10.28991/CEJ-2022-08-07-01 Full Text: PDF